Adaptation of Cloud Accounting in SMEs: Institutional Isomorphism Perspective - Mahardhika, Arya Samudra; Siahaan, Nur Halimah (Jurnal Akuntansi Manado (JAIM), 2024)
This study examines the influence of Mimetic Pressure, Coercive Pressure, and Normative Pressure on the intention and behavior of using cloud accounting in SMEs in Kebumen Regency using the Institutional Theory approach. The hypotheses in this study were tested using Structural Equation Modelling (SEM) with Smart PLS. The respondents were 43 SME owners. The results show that Mimetic Pressure and Normative Pressure do not influence the intention to use cloud accounting, while Coercive Pressure has a positive influence. The intention to use has a positive influence on the behavior of use. This study suggests that external pressure can be an effective strategy to promote the adoption of cloud accounting.